2015
DOI: 10.1111/1751-7915.12302
|View full text |Cite
|
Sign up to set email alerts
|

The acid adaptive tolerance response in Campylobacter jejuni induces a global response, as suggested by proteomics and microarrays

Abstract: Campylobacter jejuni CI 120 is a natural isolate obtained during poultry processing and has the ability to induce an acid tolerance response (ATR) to acid + aerobic conditions in early stationary phase. Other strains tested they did not induce an ATR or they induced it in exponential phase. Campylobacter spp. do not contain the genes that encode the global stationary phase stress response mechanism. Therefore, the aim of this study was to identify genes that are involved in the C. jejuni CI 120 early stationar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Organic acids are regularly used to remove foodborne bacteria from poultry carcasses in the United States [28,29,30]. However, many foodborne pathogens have acid stress mechanisms that can help them adapt to varying pH environments [38,65,66,67,68]. Campylobacter jejuni has the gene make-up required to induce an acid-tolerance response [68].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Organic acids are regularly used to remove foodborne bacteria from poultry carcasses in the United States [28,29,30]. However, many foodborne pathogens have acid stress mechanisms that can help them adapt to varying pH environments [38,65,66,67,68]. Campylobacter jejuni has the gene make-up required to induce an acid-tolerance response [68].…”
Section: Discussionmentioning
confidence: 99%
“…However, many foodborne pathogens have acid stress mechanisms that can help them adapt to varying pH environments [38,65,66,67,68]. Campylobacter jejuni has the gene make-up required to induce an acid-tolerance response [68]. In addition, there is an increase of acid tolerance in C. jejuni caused by coincubation with protozoa [69], and the genes involved in iron control and uptake are also induced [67,68].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron uptake in C. jejuni may be generally related to acid tolerance and antibiotic survival. Transcriptomic and proteomic studies have shown that this iron uptake system, in addition to several other iron uptake genes ( cfbpA / B , ceuE , and chuZ ), was more highly expressed upon C. jejuni exposure to acid stress ( 74 , 75 ). In addition, deletion of fur increased C. jejuni sensitivity to acidic conditions ( 76 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that C. jejuni possesses a robust regulatory system and stress-protective mechanisms, which enable its survival in hostile conditions within and outside the host [Svensson et al, 2008]. For subsets of genes that encode proteins, a global change in gene expression was observed in responses to heat shock, alkaline shock, and oxidative stress during the stationary phase [Wright et al, 2009]; however, C. jejuni lacks the RNA polymerase sigma factor (RpoS), which regulates stress response in the stationary phase in other bacteria [Turonova et al, 2017;Varsaki et al, 2015]. In addition to the above-mentioned stress factors, C. jejuni must overcome aerobic conditions.…”
Section: Qs and Stress Responsesmentioning
confidence: 99%